Integrating the Eco Explorers Game to Enhance Elementary Students’ Problem-Solving Skills in Ecosystem Learning - Intan Meifilindati; Ika Maryani; Okimustava Okimustava; Muhammad Kristiawan; Josephine Magay Salmo (Jurnal VARIDIKA, 2025)
Science education at the primary level plays a critical role in fostering students’ higher-order thinking skills, particularly their problem-solving abilities. However, many elementary students continue to face challenges in developing these competencies, leading to generally low levels of performance. This study investigates the effectiveness of the Eco Explorers educational game in enhancing the problem-solving skills of fifth-grade students within the topic of ecosystems. A pre-experimental one-group pretest-posttest design was employed, involving 25 participants selected through a non-probability sampling technique. Data were collected using observation sheets and standardized problem-solving tests, and analyzed using descriptive statistics, paired sample t-tests, and effect size calculations (Cohen’s d) with SPSS version 26. The results revealed a statistically significant improvement in students’ problem-solving abilities (p = 0.000 < 0.05), with a large effect size (Cohen’s d = 2.55). These findings reinforce previous studies highlighting the benefits of game-based learning for cognitive development. In conclusion, the Eco Explorers game is a highly effective instructional tool for improving students’ problem-solving skills in science education, particularly within ecological contexts. The study implies that incorporating interactive digital games into science instruction can significantly enhance student engagement and higher-order thinking, ultimately supporting more meaningful and effective learning experiences in primary education.